First Experience of Three Neurovascular Centers With the p64MW-HPC, a Low-Profile Flow Diverter Designed for Proximal Cerebral Vessels With Antithrombotic Coating - Winters, Helge; Schüngel, Marie-Sophie; Scherlach, Cordula; Mucha, Dirk; Thalwitzer, Jörg; Härtig, Wolfgang; Donitza, Aneta; Bailis, Nikolaos; Maybaum, Jens; Hoffmann, Karl Titus; Quäschling, Ulf; Schob, Stefan (Frontiers in Neurology, 2021)
Background In the last decade, flow diversion (FD) has been established as hemodynamic treatment for cerebral aneurysms arising from proximal and distal cerebral arteries. However, two significant limitations remain - the need for 0.027” microcatheters required for delivery of most flow diverting stents (FDS), and long-term dual anti-platelet therapy (DAPT) in order to prevent FDS-associated thromboembolism, at the cost of increasing the risk for hemorrhage. This study reports the experience of three neurovascular centers with the p64MW-HPC, a FDS with anti-thrombotic coating that is implantable via a 0.021” microcatheter. Materials and methods Three neurovascular centers contributed to this retrospective analysis of patients who were treated with the p64MW-HPC between 03/2020 and 03/2021. Clinical data, aneurysm characteristics and follow-up results, including procedural and post-procedural complications, were recorded. The hemodynamic effect was assessed using the O`Kelly-Marotta-Scale (OKM). Results 32 patients (22 female, mean age 57.1y) with 33 aneurysms (27 anterior circulation, 6 posterior circulation) were successfully treated with the p64MW-HPC. In 30/32 patients (93.75%), aneurysmal perfusion was significantly reduced immediately post implantation. Follow-up imaging was available for 23 aneurysms. Delayed aneurysm perfusion (OKM A3: 8.7%), reduction in aneurysm size (OKM B1-3: 26.1%) or sufficient separation from the parent vessel (OKM C1-3 and D1: 65.2%) were demonstrated at the last available follow-up after a mean of 5.9 months. In 2 cases, device-thrombosis after early discontinuation of DAPT occurred. One delayed rupture caused a caroticocavernous fistula. The complications were treated sufficiently and all patients recovered without permanent significant morbidity. Conclusion Treatment with the p64MW-HPC is safe and feasible and achieves good early aneurysm occlusion rates in the proximal intracranial circulation, which are comparable to those of well-established FDS. Sudden interruption of DAPT in the early post-interventional phase can cause in-stent-thrombosis despite the HPC surface-modification. Deliverability via the 0.021” microcatheter facilitates treatment in challenging vascular anatomies.